An Overview of Legal Provisions regarding Legal Literacy in Nepal - Panta, Binita Devi (Ganeshman Darpan, 2022)
This paper analyzes the legal provisions pertaining to legal literacy in Nepal. In order to practice existing laws and retain the rule of law in the state, basic understanding of law among people is crucial. In the context of Nepal, the rights and obligations granted by the constitution are still unrealized by its people. Moreover, people are intimidated and alienated from law knowingly or ignorantly. In the same way, access to justice for the ordinary populace seems unachievable. Similarly, service deliveries trends of state are often being experienced partial and discriminatory. Lack of legal knowledge could be the significant reason behind all these challenges. Thus, the researcher argues that, until and unless the state makes a specific provision regarding legal literacy and executes them practically, the attainment of rule of law is unthinkable. In this paper, the existing constitution and its legal provisions, programs and policies related to legal practice and legal literacy have been examined to ascertain the state’s attempt regarding legal literacy. The researcher concludes that legal awareness is an indispensable part of rule of law, which contributes to developing the self-realization among individuals and further enables them to participate in the governance process.